PENGEMBANGAN BOARD GAME KEKAYAAN BUDAYA INDONESIA DALAM MENINGKATKAN HASIL BELAJAR IPAS KELAS IV MI RADEN FATAH - Aziza, Nur (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2024)
Learning media acts as an intermediary for teachers in conveying learning content to students and facilitating student understanding. Learning media plays an important role in learning in elementary schools, such as science and science learning for fourth grade students. One of the learning media that teachers can use in science learning is board game learning media. The objectives of the research carried out are: 1. To find out the process of developing board game learning media in science subjects on Indonesian cultural riches; 2. Knowing the attractiveness of the board game learning media being developed; 3. Knowing the effectiveness of board game learning media in improving student learning outcomes. This research is a type of development research or Research and Development (R&D) with the Borg & Gall model. The research subjects were fourth grade students at MI Raden Fatah Malang. The material presented in the media is the richness of Indonesian culture in science subjects. Data collection techniques were carried out using interviews, questionnaires and tests. Data analysis techniques were carried out using quantitative, qualitative data analysis and the N-gain test. Based on the research results, the learning media developed received 92% validation in terms of material, 97.3% in terms of media design, and 85.3% in terms of learning. The attractiveness of learning media for all students was assessed at 89.7%, which shows that learning media is very interesting for students. Student learning outcomes also increased from an average pre-test score of 46.1 to an average post-test score of 74.3. Increased student learning outcomes in Indonesian cultural wealth material based on the average N-gain analysis results (0.538036686). It can be concluded that board game learning media can improve learning outcomes in science subjects for class IV students at MI Raden Fatah Malang. ABSTRAK Media pembelajaran berperan sebagai perantara guru dalam menyampaikan isi pembelajaran kepada siswa dan memudahkan pemahaman siswa. Media pembelajaran memegang peranan penting dalam pembelajaran di sekolah dasar, seperti pembelajaran IPAS untuk siswa kelas IV. Salah satu media pembelajaran yang dapat digunakan guru dalam pembelajaran IPAS adalah media pembelajaran board game. Tujuan dari penelitian yang dilakukan adalah: 1. Untuk mengetahui proses pengembangan media pembelajaran board game pada mata pelajaran IPAS pada materi kekayaan budaya Indonesia; 2. Mengetahui daya tarik media pembelajaran board game yang dikembangkan; 3. Mengetahui efektivitas media pembelajaran board game dalam meningkatkan hasil belajar siswa. Penelitian ini merupakan jenis penelitian pengembangan atau Research and Development (R&D) dengan model Borg & Gall. Subjek penelitian adalah siswa kelas IV MI Raden Fatah Malang. Materi yang disajikan dalam media adalah kekayaan budaya Indonesia pada mata pelajaran IPAS. Teknik pengumpulan data dilakukan dengan menggunakan wawancara, angket, dan tes. Teknik analisis data dilakukan dengan menggunakan analisis data kuantitatif, kualitatif, dan uji N-gain. Berdasarkan hasil penelitian, media pembelajaran yang dikembangkan memperoleh validasi 92% dari segi materi, 97,3% dari segi desain media, dan 85,3% dari segi pembelajaran. Daya tarik media pembelajaran bagi seluruh siswa dinilai sebesar 89,7% yang menunjukkan bahwa media pembelajaran sangat menarik bagi siswa. Hasil belajar siswa juga meningkat dari rata-rata skor pre-test sebesar 46,1 menjadi rata-rata skor post-test sebesar 74,3. Peningkatan hasil belajar siswa pada materi kekayaan budaya Indonesia berdasarkan rata-rata hasil analisis N-gain (0,538036686). Dapat disimpulkan bahwa media pembelajaran board game dapat meningkatkan hasil belajar mata pelajaran IPAS siswa kelas IV MI Raden Fatah Malang.